Neurotypicals with higher autistic traits have delayed visual processing of an approaching life-sized avatar’s gait: an event-related potentials study - Inokuchi, Ryo; Ichikawa, Hiroko; Yamamoto, Masataka; Takemura, Hiroshi (Frontiers in Human Neuroscience, 2023)
Introduction Autism spectrum disorder (ASD) is a neurodevelopmental disorder, which is reportedly related to difficulties in the visual processing of human motion, such as biological motion and gestures. Moreover, neurotypical (here, we mention it as individuals without a diagnosis) adults with autistic traits are clumsier than those without autistic traits when passing by others. It is still unclear whether the clumsiness derived from atypical visual processing of another’s approaching gait motion. We aim to address this question by investigating the association between autistic traits in neurotypical adults and the visual processing of an approaching life-sized avatar’s gait. Methods We clarified a typical visual motion processing and autistic traits in daily life in 26 neurotypical adults by analyzing the subthreshold autism trait questionnaire (SATQ) score, a 24-item self-report scale of ASD, and event-related potentials (ERPs) in response to walking motion of a passing avatar. Videos of walking life-sized virtual avatars approaching and retreating were presented as visual stimuli. Results and discussion The association between the participants’ SATQ scores and the latencies and amplitudes of the ERPs was examined. ERP components (N170 and P200) components were identified at T5 and T6 electrodes. Participants reporting higher SATQ scores had longer latencies of P200 at T6 and lower amplitudes of P200 at T5 and T6 electrodes for the approaching avatar than those reporting lower SATQ scores. These findings indicate that adults with autistic traits have delayed and less sensitive visual processing of the approaching avatar. It suggests that while passing another person, these individuals have atypical visual processing of their approach. This study may contribute to elucidating autistic traits from the perspective of visual processing in an environment simulating daily life.